Ascorbic Acid and Glucosinolate Levels in New Czech Cabbage Cultivars: Effect of Production System and Fungal Infection - Cenek Novotny (Molecules, 2018)
Nutritional value and disease-preventive effects of cabbage are well-known. Levels of the antioxidant compounds ascorbic acid (AA) and glucosinolates (GSL) in new Czech cabbage cultivars were determined in the context of different production systems. The contents of AA and GSLs in cabbage biomass were determined by HPLC. Individual GSLs were identified according to their exact masses with sinigrin used as the external standard. Artificial infection with A. brassicicola generally raised the AA levels. The major GSLs (≥10 mg kg−1) were glucobrassicin, sinigrin, and glucoiberin. Indole and aliphatic GSLs were present, but no aromatic ones were detected. Ecological growth conditions and the artificial fungal infection increased the total content of GSLs and, also, of the methoxylated indole GSLs. Sulforaphane, iberin, indole-3-carbinol, and ascorbigen resulting from the hydrolysis of GSLs were found in both cultivars. The amounts and profiles of GSLs present in the two Czech cultivars demonstrated their good nutritional value. The decomposition products sulforaphane, iberin, indole-3-carbinol, and ascorbigen detected improve its health-promoting qualities and represent a suitable component of the human diet.